RESEARCH AND COMMUNITY SERVICE PERFORMANCE IMPROVEMENT STRATEGY: A STUDY OF THE FACULTY OF AGRICULTURE, UNIVERSITAS SEBELAS MARET (UNS) - Setyowati, Nuning; Fauza, Gusti; Rusdiyana, Eksa; Yudhistira, Bara; Sujarwo, Rakhma Melati (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2025)
Research and community service performance are key indicators of a college's quality. This Research aims to analyze performance and formulate alternative improvement strategies for P2M performance of lecturers at the Faculty of Agriculture, UNS. This Research employs a descriptive qualitative method, utilizing key informants who are stakeholders in the agricultural faculty at UNS. Primary data consists of strengths, weaknesses, opportunities, and threats related to P2M and supported by secondary P2M data. Results show that P2M performance is generally already relatively good. However, some aspects of performance, such as Scopus publications, patents, and books, still need improvement. Alternative strategies formulated are the SO strategy: improvement of competence achievement, grant research, and community service at internal, external, and international levels, improvement of actualization of P2M through international indexation, utilization of journals at the faculty for increasing global cooperation, and increasing the contribution of lecturers in the food self-sufficiency program. WO Strategy: Optimizing the utilization of assets to capture demand opportunities for agricultural-based products as a source of income-generating, increasing the participation and capabilities of lecturers in international publications. ST Strategy: Increasing personal productivity and strengthening P2M innovation to encourage commercialization of research results, optimizing the role of lecturers to increase competitiveness in the external environment, strengthening branding through international publications, and improving the quality of journal media. WT Strategy: Monitoring and evaluation of collaboration sustainability and develop partnerships with external parties, developing innovation and strengthening commercialization through increasing the number of patents and books.